Beyond financial performance: A perspective on occupational safety performance in automobile SMEs in Nigeria - Sakariyau, Olalekan Busra; Hamrila, Abdul Latip (Consortia Academia Publishing, 2016)
Previous studies of SMEs have found that accounting, finance, production and marketing take precedence over personnel related issues like safety and health. There has been a long standing interest in finding ways to assist SMEs in improving safety and health. The aim of this study was to assess the occupational safety performance in automobile SMEs in Abuja, Nigeria. The research method is descriptive - survey. The population consisted of all employees in the department of works and maintenance within 46 automobile SMEs. The results indicate that health and safety which is a crucial characteristic and component in the organization need to be improved upon. The entrepreneurs and owners in this enterprise need to inculcate safety leadership supports as part of their strategies to boost employees’ health morale and job satisfaction.